Exosomes in liver fibrosis: The role of modulating hepatic stellate cells and immune cells, and prospects for clinical applications - Liu, Yufei; Zheng, Yuhong; Yang, Yang; Liu, Ke; Wu, Jianying; Gao, Peiyang; Zhang, Chuantao (Frontiers in Immunology, 2023)
Liver fibrosis is a global health problem caused by chronic liver injury resulting from various factors. Hepatic stellate cells (HSCs) have been found to play a major role in liver fibrosis, and pathological stimuli lead to their transdifferentiation into myofibroblasts. Complex multidirectional interactions between HSCs, immune cells, and cytokines are also critical for the progression of liver fibrosis. Despite the advances in treatments for liver fibrosis, they do not meet the current medical needs. Exosomes are extracellular vesicles of 30-150 nm in diameter and are capable of intercellular transport of molecules such as lipids, proteins and nucleic acids. As an essential mediator of intercellular communication, exosomes are involved in the physiological and pathological processes of many diseases. In liver fibrosis, exosomes are involved in the pathogenesis mainly by regulating the activation of HSCs and the interaction between HSCs and immune cells. Serum-derived exosomes are promising biomarkers of liver fibrosis. Exosomes also have promising therapeutic potential in liver fibrosis. Exosomes derived from mesenchymal stem cells and other cells exhibit anti-liver fibrosis effects. Moreover, exosomes may serve as potential therapeutic targets for liver fibrosis and hold promise in becoming drug carriers for liver fibrosis treatment.